Legal Analysis of Cartoon Film Copyright Violations in Free Movie Streaming Services - Gelora, Rifqi Ananda; Parmitasari, Indah (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The bad impact of free movie streaming services is the Author or Copyright Holder does not get royalties for the use of his or her creation as well as moral rights because the name of the Author on the film streaming services is not included as something attached to the Work.Purposes of the Research: The purpose of this study is to figure out whether or not the publication of cinematographic works in the form of cartoons on free movie streaming services is an unlawful act. This study also aims to investigate the efforts to prevent copyright infringement of cartoon films distributed by other parties in free movie streaming services.Methods of the Research: The research method used is normative legal research with a statute legal approach.Results of the Research: The result of this study includes 2 (two) things. This study found that the publication of cartoons in free movie streaming services is an act against the law because it violates Copyright Law which causes harm to the Author or Copyright Holder. Moreover, the results of this study also explain the various efforts to prevent copyright infringement on cartoon films distributed by other parties in free movie streaming services.